Analysis of Paper Fiber Types based on Color Change - Juwairiah, Juwairiah; Sinambela, Yusnia; Sitorus, Nurianti; Gobal, Raju (Proceeding International Conference on Religion, Science and Education, 2024)
This study aims to see the paper fiber and how the strength of the paper fiber from a visual perspective. The paper fibers tested consisted of ten different types of paper, with the principle that the Phloroglucin solution consisted of Phloroglucin powder, HCl, and Alcohol. Lignin when reacted with Phloroglucin solution will change to a purplish red color which indicates that the paper comes from mechanical fibers (contains wood). Based on the test results of newsprint, casing paper and board paper changed to a purplish red color which indicates that the paper comes from mechanical fibers (contains wood). Meanwhile, HVS paper, art paper, BC Putih paper, ivory paper and doshlag paper did not change color, which means that there was a chemical process to remove wood resin or lignin from the paper.